Technological Literacy Improvement Program for Students Through Introduction to the Basics of Computer Vision: Program Peningkatan Literasi Teknologi untuk Mahasiswa Melalui Pengenalan Dasar-Dasar Computer Vision - Harun Al Azies; Muhammad Naufal; Danar Cahyo Prakoso; Novianto Nur Hidayat (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2024)
This activity fills the knowledge gap in students' fundamental grasp of computer vision by emphasizing direct engagement with daily technologies. The major objective is to raise students' technology literacy and equip them to become future leaders with contextually applicable knowledge of computer vision. This program, which involves 170 students, consists of seminars, workshops, and on-the-job training. Statistical tests, such as the Wilcoxon test, are used in the analysis process to compare understanding levels before and after the activity. The Wilcoxon test regularly confirmed significant differences and statistical data demonstrated a considerable gain in computer vision literacy among participants. A comprehensive picture of how student comprehension has changed is provided by descriptive analysis. Analyzing statistical data confirms how well the activities alter participants' perceptions, to have a long-term effect on the advancement of technology and society development.